A MATTER OF DEMOCRACY: UNITY OF ETHICL LIFE AS A LIFE WORTHY FOR ONESELF AND FOR OTHERS (Isagoge - Journal of Humanities and Social Sciences, 2022)
This paper presents the living well concept of Ronald Dworkin, from the work Justice for Hedgehogs (2011), in which he defends a thesis of unity of ethical and moral values. With theoretical influences of Immanuel Kant, the philosopher starts from what he understands as ideal of dignity. Through a bibliographical research conducted under the hypothetical-deductive method, this study (i) evidences the Dworkin's theory and his kantian inspiration, (ii) demonstrates that it is a mature theory to understand human dignity as a foundation for a liberal equality democracy.